Thyroid gland with a separate left lobe - (:unkn) unknown (My University, 2000)
During routine dissection of a 50 year-old male cadaver, we encountered a developmental anomaly of the thyroid gland having a left lobe connected to the isthmus by the thyroid fascia. Glandular tissue was not observed within the fascial connection. Right and left lobes were asymmetric, with heights of 83 mm and 52 mm, respectively. The gland was supplied by superior and inferior thyroid arteries, while the isthmus was supplied by branches of the right superior and inferior thyroid arteries. The thyroidea ima artery was not observed.
Keywords: Isthmus; Thyroid gland; Variation